The recurrent campylobacteriosis epidemic over Christmas and New Year in European countries, 2006–2014 - Bless, Philipp Justus (BMC Res Notes, 2017)
OBJECTIVE: Campylobacteriosis is the most frequently reported foodborne disease in Europe with a notification rate of 71 per 100,000 population in the European Union in 2014. Surveillance data show a clear seasonality whereby case numbers peak during summer months in entire Europe and at the turn of the year, especially in Germany and Switzerland. A detailed description of European surveillance data by country at the turn of the year was missing so far. The objectives of the presented work were to describe national surveillance data of The European Surveillance System for 14 countries during winter times and to generate hypotheses for the observed seasonality of campylobacteriosis cases. RESULTS: The analysis included 317,986 cases notified between calendar weeks 45 and 8 of winter seasons 2006/2007–2013/2014. Winter peaks in weekly case notifications and notification rates were observed for Austria, Belgium, Finland, Germany, Luxembourg, The Netherlands, Switzerland and Sweden while for Denmark, France, Ireland, Italy, Norway and the United Kingdom no unusual increase was observed. Generally, weekly notification rates peaked in calendar week 1 or 2 after a strong decline in the last week of December and reached values of a multiple of the observed notification rates in the weeks before or after the peak e.g. up to 6.5 notifications per 100,000 population per week in Luxembourg. Disease onset of cases notified during winter peaks occurred predominantly in calendar weeks 52 and 1 and point towards risk exposures around Christmas and New Year. The consumption of meat fondue or table top grilling poses such a risk and is popular in many countries with an observed winter peak. Additionally, increased travel activities over the festive season could foster campylobacteriosis transmission. Surveillance artefacts (e.g. reporting delays due to public holidays) should be excluded as causes for country-specific winter peaks before investigating risk exposures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-017-2587-8) contains supplementary material, which is available to authorized users.